2005
DOI: 10.1016/j.amepre.2004.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Selected nonvaccine interventions to prevent infectious acute respiratory disease

Abstract: Promoting hand hygiene and reducing crowding through the provision of adequate living space and cohorting of training units may offer benefits in respiratory disease control. These interventions, along with UV lights and air dilution/ventilation, deserve further evaluation in controlled studies to assess their efficacy. NOVARDIs could benefit military and other populations living in close contact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 48 publications
(52 reference statements)
0
25
0
Order By: Relevance
“…For the sake of clarity, the term "FRI" will be used in the remainder of this paper. Close living conditions, environmental exposures, physical challenges, stress, constant introduction of immunologic naives, and hygienic challenges are considered important factors that make military populations vulnerable to infectious diseases [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…For the sake of clarity, the term "FRI" will be used in the remainder of this paper. Close living conditions, environmental exposures, physical challenges, stress, constant introduction of immunologic naives, and hygienic challenges are considered important factors that make military populations vulnerable to infectious diseases [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…The intense burden of respiratory disease found in the recruit setting may also play a role in the differences between recruits and non-recruits. Crowded living conditions, stressful environments, and the continuous entry of people from throughout the United States into this population make this setting ideal for the spread of respiratory pathogens [38,39]. Not surprisingly, we found rates of ILIs to be 2-16 times higher among the recruits compared to the non-recruits depending on the service, immunization group, analysis cohort, and year of study.…”
Section: Discussionmentioning
confidence: 57%
“…If time and sink/facility limitations exist, instant hand sanitizers have shown a significant advantage over traditional antimicrobial soap (Dyer, Shinder, & Shinder, 2000;Dyer, Gerenratch, &Wadhams, 1998;Lee, Jordan, Sanchez, & Gaydos, 2005;White et al, 2001;White et al, 2005;FDA, 2003). Additionally, hand hygiene with the use of hand sanitizers will result in less skin irritation and will minimize time constraints (Boyce et al, 2000).…”
Section: Chapter 2 -Literature Reviewmentioning
confidence: 99%
“…Studies have also demonstrated the effectiveness of instant hand sanitizers in reducing illness (Doebbeling et al, 1992;Dyer et al, 2000;Guinan, McGuckin, & Ali, 2002;Larson, Cimiotti, Haas, Parides, Nesin, Della, & Saiman, 2005;Lee et al, 2005;White et al, 2001;White et al, 2005). The CDC (2002) has recommended that using alcohol-based hand sanitizers is acceptable if hands are not visibly soiled (Boyce & Pittet, 2002).…”
Section: Guidelines For Hand Hygiene In Health Carementioning
confidence: 99%
See 1 more Smart Citation